Molecular Analysis and Effectiveness Assay of AV1 Gene in Transgenic Tobacco for Resistance to Begomovirus - Tri Joko Santoso; Muhammad Herman; Sri H. Hidayat; Hajrial Aswidinnoor; Sudarsono Sudarsono (Jurnal AgroBiogen, 2012)
Genetic transformationof tobacco plant using AV1 gene was conducted atthe previously experiment and generated transgenic tobaccoplants positively carrying the selectable marker nptII gene.The objectives of this experiment were to (1) analyze thepresence of Begomovirus AV1 gene in T0 generation putativetransgenic tobacco plants using PCR technique with specificprimers and its correlation with resistance phenotype, (2)analyze the integration and copy number of the transgene inT0 generation putative transgenic tobacco plants and itscorrelation with resistance response, (3) screen the T0generation putative transgenic tobacco plants with the targetvirus infection and to detect the presence of the virus in thetransgenic plant tissue using universal primers. PCRdetection of AV1 gene in tobacco transgenic was conductedby using specific primer for Begomovirus AV1 gene.Meanwhile, Southern Blot analysis was conducted by usingthe AV1 gene probe. The effectiveness of AV1 gene intobacco transgenic was tested by inoculation of target virususing whiteflies vector. Result of the experiments showedthat there was a positive correlation between the presenceof the AV1 transgene in T0 generation putative transgenictobacco plants and the resistant phenotype. Transgenicplants with a single copy integration of the transgeneexhibited more resistant than the multiple copy one. andnon transgenic plant. The resistance as a result of AV1 geneexpression was indicated with no symptom in T0 generationtransgenic tobacco plants and the accumulation of the virusin the transgenic plants tissue. Northern and Westernhybridization analysis need to be perfomed for investigatingthe presence of mRNA or protein accumulation so that theresistance mechanism of the AV1 gene could be explainedmore detail.